Species‐specific effects of subdaily temperature fluctuations on consumption, growth and stress responses in two physiologically similar fish species. Issue 3 (21st April 2015) - Coulter, David P.; Sepúlveda, Maria S.; Troy, Cary D.; Höök, Tomas O.
Abstract: Fluctuations in water temperature can have important physiological consequences for fishes. Effects of daily thermal cycles are well studied and can be beneficial, increasing prey consumption and growth rates when mean and maximum temperatures of the fluctuations are at or below the species' optimum temperature. While less studied, subdaily temperature fluctuations are also common in many aquatic habitats and can be caused by both natural and anthropogenic processes. We performed laboratory experiments to examine how two fish species (yellow perch, Perca flavescens, and walleye, Sander vitreus ) with similar thermal preferences respond to chronic exposure to subdaily temperature variability. We selected temperature treatments that reflected observed thermal variation after examining water temperature data from multiple aquatic systems. We then separately exposed yellow perch and walleye to a stable 23 °C treatment and 12‐h cycles of 23 ± 2 °C or 23 ± 4 °C for 45 days. Adult yellow perch exposed to fluctuations of 23 ± 4 °C over 12 h expressed higher consumption, growth and food conversion efficiency than fish experiencing stable 23 °C. Temperature fluctuations, though, resulted in mortalities and the development of skin ulcers in yellow perch that did not occur under stable temperatures. In contrast, the same 12‐h temperature fluctuations did not result in mortalities or stress responses in juvenile walleye. Moreover, unlike yellow perch, growth rates of walleye were lower under 12‐h temperature fluctuations compared with the stable 23 °C treatment. Our results indicate that species with similar thermal preferences can respond differently to the same subdaily temperature fluctuations.